Varying performance of eight evapotranspiration products with aridity and vegetation greenness across the globe - Wang, Hongzhou; Li, Xiaodong; Tong, Cheng; Xu, Yongkang; Lin, Dongjun; Wang, Jiazhi; Yao, Fei; Zhu, Pengxuan; Yan, Guixia (Frontiers in Environmental Science, 2023)
The wide application of the evapotranspiration (ET) products has deepened the understanding of the water, energy and carbon cycles, which consequently has drawn the attention to the regional or global assessments on the quality of ET products, producing a large number of studies. However, little is known about how the performances of the ET products vary with the aridity and vegetation greenness, especially at the global scale. In this study, employing the water balance methods and the metric–Kling-Gupta efficiency (KGE), we evaluated eight ET products across the global 1381 basins; these ET products are derived from Global LAnd Surface Satellite (GLASS), the fifth gen-eration of European ReAnalysis, version Land (ERA5-Land), Modern Era Retrospective-Analysis for Research and Applications, version 2 (MERRA-2), Global Land Evaporation Amsterdam Model, version 3.5a (GLEAM-3.5a), the ensemble of EartH2Observe products generated by ten models (E2O-En), Penman-Monteith-Leuning (PML), Global Land Data Assimilation System, version Noah (GLDAS2.0-Noah), Model Tree Ensemble (MTE). The results indicated that i) the ET products could capture the mean annual ET, among which the PML performed the best with 0.89 for KGE, but had limited capacity to reproduce the ET temporal variability and trend; ii) temporally, the overall performances of the ET products for each basin were still low with basin-averaged negative KGE value; iii) at the regional scale, the spatial and temporal performances of the ET products were strongly affected by aridity and vegetation greenness. It is worth noting that the poorer perfor-mance occurred in wet regions or lush vegetation regions; therefore, we highlight the strong impact of aridity and vegetation greenness on the ET products, under the condition of continuing global (regional) warming and greening. Which hopefully will contribute to the directional op-timizations and effective applications of ET simulations.